Single-Cell Transcriptomic Analysis Reveals Mitochondrial Dynamics in Oocytes of Patients With Polycystic Ovary Syndrome - Qi, Lingbin; Liu, Boxuan; Chen, Xian; Liu, Qiwei; Li, Wanqiong; Lv, Bo; Xu, Xiaoyu; Wang, Lu; Zeng, Qiao; Xue, Jinfeng; Xue, Zhigang (Frontiers in Genetics, 2020)
Polycystic ovary syndrome (PCOS), characterised by polycystic ovarian morphology, ovarian follicular maturation arrest, and hormonal disorders, affects numerous women in the reproductive age worldwide. A recent study has found that mitochondria are likely to play an essential role in oocyte quality. However, it is still unclear whether oocyte development failure is associated with mitochondria in patients with PCOS. We analysed the single-cell RNA sequencing data from the previous study, including data from 14 oocytes from 7 healthy fertile women and 20 oocytes from 9 patients with PCOS at the germinal vesicle (GV) stage, metaphase I (MI) stage, and metaphase II (MII) stage. We revealed the transcriptomic dynamics by weighted gene co-expression network analysis (WGCNA) and investigated the differences between stages using PCA and Deseq2 analyses to identify the differential expression genes (DEGs). Gene ontology (GO) was performed using clusterProfiler R package and Metascape. Our results indicated that specific gene modules were related to different stages of oocyte development using WGCNA. Functional enrichment analysis and gene co-expression network analysis found significant enrichment of the mitochondrial regulation genes at the GV stage. PCA (principal component analysis) and differential gene expression analysis suggested that GV was significantly different from the MI and MII stages between the two groups. Further analysis demonstrated that the upregulated differentially expressed genes at the GV stage of patients with PCOS mainly related to mitochondrial function, such as COX6B1, COX8A, COX4l1, and NDUFB9. Meanwhile, these genes tended to be activated at the MII stage in healthy cells, suggesting that some mitochondrial functions may be prematurely activated at the GV stage of PCOS oocytes, whereas this process occurs at the MII stage in healthy oocytes. Collectively, our study showed that aberrant mitochondrial function at the GV stage may contribute to a decline in oocyte quality of PCOS patients.